Quantitative determination of fenoterol and fenoterol derivatives in rat plasma using on-line immunoextraction and liquid chromatography/mass spectrometry - Kim, Hee Seung (2008)
An on-line immunoextraction and liquid chromatography/mass spectrometry (LC/MS) method was developed and validated for the determination of R,R′-fenoterol, R,R′-methoxyfenoterol and R,S′-naphthylfenoterol in rat plasma. Sample preparation involved immunoextraction of analytes using an antibody raised against R,R′- and R,S′-aminofenoterol that was immobilized onto chromatographic support. LC was performed on a Waters hydrophilic interaction chromatography (HILIC) column (150 mm × 2.1 mm), using an isocratic mobile phase of methanol:ammonium acetate (10 mM, pH 6.8) (90:10, v/v) at a flow rate of 0.2 ml/min. The MS was operated in the single ion monitoring mode (m/z 304.2 for R,R′-fenoterol, m/z 318.1 for R,R′-methoxyfenoterol, and m/z 339.2 for R,S′-naphthylfenoterol). Optimization of analytes desorption process from the immunoextraction column was performed by factorial analysis and the sample calibration curves were made with spiked rat plasma samples containing 0.5−100 ng/ml of drugs. The cross-selectivity studies of the antibody were determined and the results suggested high selectivities toward R,R′-fenoterol, R,R′-methoxyfenoterol and R,S′-naphthylfenoterol. The accuracy of assay was more than 96% while intra- and inter-day precision of assay were less than 12.4%. Stability studies (2 h benchtop, freeze/thaw, and autosampler stability) were conducted and the analytes were stable through out studies. The validated method was used to determine the plasma concentration–time profiles of drugs after oral administration to rats of R,R′-fenoterol, R,R′-methoxyfenoterol and R,S′-naphthylfenoterol.